Sterile Seroma after Drainage of Purulent Muscle Abscess in Crohn’s Disease: Two Cases - Natasha Shah; Lara Dakhoul; Adam Treitman; Muhammed Tabriz; Charles Berkelhammer (Case Reports in Gastrointestinal Medicine)
Purulent skeletal muscle abscesses can occur in Crohn’s disease. We report a case of a sterile seroma complicating percutaneous drainage of a purulent skeletal muscle abscess in Crohn’s ileitis. We compare and contrast this case with a similar case we published earlier. We emphasize the importance of recognition and differentiation from a septic purulent abscess.